Fatty Acid Profiles of Serum Lipid Fractions Change Minimally in Sled Dogs Before and After Short Bouts of Exercise - Templeman, James R.; Trevizan, Luciano; Ma, David W. L.; Shoveller, Anna K. (Frontiers in Veterinary Science, 2021)
Although emerging data suggests a greater influence of gluconeogenic precursors, endurance sled dogs have long appeared to rely heavily on fatty acid oxidation for sustained energy production. However, much of the research investigating lipid utilization during exercise in sled dogs has been carried out with dogs subjected to extended bouts of endurance exercise. Less is known about changes in fatty acid composition in endurance training sled dogs subjected to short bouts of exercise, and fewer data define how fatty acid composition may change in distinct lipid fractions. As such, the study objective was to assess whether short bouts of submaximal exercise would affect fatty acid profiles of serum lipid fractions in endurance training sled dogs. Fifteen privately-owned Siberian huskies were used (8 females: 4 intact, 4 spayed; 7 males: 2 intact, 5 neutered), with an average age of 4.6 ± 2.5 years and body weight of 24.8 ± 4.2 kg. Throughout the diet acclimation and remainder of the study, all dogs were fed a dry extruded diet that met or exceeded all AAFCO nutrient recommendations. Dogs were weighed weekly and fed to maintain baseline body weight. A 12‐week exercise regimen was designed to incorporate weekly increases in running distance, but weather played a role in setting the daily distance. On weeks 2, 5, and 11, an exercise challenge was implemented whereby dogs would run 4 km at 15 km/hr in teams of 4. Pre- and post-exercise blood samples were taken, and gas chromatography was used to evaluate fatty acid profiles of all identified serum lipid fractions (cholesterol ester, diacylglycerol, free fatty acid, phospholipids, triglyceride). Data were analyzed using PROC MIXED of SAS, with dog as a random effect and week and sampling time point as fixed effects. Composition of oleic (18:1n9), linoleic (18:2n6), and alpha-linolenic (18:3n3) acids in the free fatty acid fraction decreased by approximately 9, 10, and 60%, respectively, following exercise (P ≤0.05). The results presented herein suggest that aside from a degree of depletion of these 18-carbon unsaturated fatty acids, short bouts of submaximal exercise do not induce considerable changes to sled dog fatty acid profiles.